(untitled) - Burghardt, M. David (Boston, 1999)
The book provides a window to the real world of engineering practice, a world of marketplace demands and tremendous opportunities. It contains four chapters. Chapter 1 examines the human-made world. Chapter 2 discusses and analyzes the design process. In chapter 3 design documentation is explored in its several forms. Chapter4 puts it all together. Engineering analysis in electrical, mechanical, and energy fundamentals is presented along with critiqued design project reports. Several fundamental software application available to engineers, essential for today's engineering practioner, are examined.
Keywords: Engineering design,Thiết kế kỹ thuật